Speaking Volumes: The Encyclopedia of Bioethics and Racism - Galarneau, Charlene (The Hastings Center report, 2022)
This essay takes as its starting point the claim that addressing anti-Black racism is essential to the work of bioethics in the United States. The essay examines whether and how racism has been addressed in the field's central reference work, the Encyclopedia of Bioethics, throughout its four editions—in 1978, 1995, 2004, and 2014. With consideration of each edition's stated purpose and editorial framing, we find that the subject of racism is obscured by the Encyclopedia's inattention to African American approaches to bioethics, to racism as a bioethics issue, and specifically, to racism as a matter of justice. This essay suggests questions for guiding reflection necessary for giving racism its due in the field of bioethics.